Caracterização dos cursos de mestrado em educação no Rio de Janeiro: um enfoque perceptivo - Brandão, Dirce de Faria (1979)
The objective of this study was to anaIyse some cha racteristics of Master Programs in Education in Rio de Janeiro, speciaIIy the ones that had been grouped in the following variabIes: cIassroom organization, teacher-student reIationship and academic advisement. A perceptive approach was taken, that is, such characteristics were got through the own graduate students' perception, considered as speciaIIy quaIified perceivers. Through a questionnaire wi th cIosed ·questions, pre- tested in advance in piIot-study, the graduate students showed their perce-ption about some characteristics of the M.a-s ter Programs and this perception was Iater reIated to variabIes of the subjects' situation. It was shown that the variabIe IIconclusion of the dissertation' seemed to infIuence in the way of percei ving the course, Ieading to a Iess criticaI point of view than the opposite situation. As the sampIe was seIected (most of subjects who had conclued the dissertation) it was possible to verify that the seIected subjects had more possibility of success even in not so favorable situations. As a matter of fact, the majority of graduate students hadn't received scholarships or any financiaI aid and had had a hard scheduIe of work ei ther during the course or during the elaboration of the dissertation. Sincc the sampIe was seIected, the variabIe seIection seemed to be the task of answering the questionnaire(and returning i t). AI though being a simpIe task, the small number of answerers (seventy-five students) scemed to have been just the more moti vatcd group, because they had been more sucCBssful and so, eager to colaborate. It is true that the student' s seIection for the cour se could be done in a different way, but it seems that practi caIly the rcsult would be the same: to seIect a group with mo re desirable charactcristics.It was concluded that it is important to select the candidates for the graduate course. Variables such as age, higher education engagement should be taken into consideration in the seIection of graduate students. However, the selection could not sorve alI the problems. In fact, the selected sample showed little criticaI ability and some acc~ptance to the system. Wouldn't these resuIts be a critic to the own system that even having motivated and high capabIe subjects (according to their academic success) gets these products? The necessity of a reformulation of the Haster Programs in Education Ieading to 'open educationl-l in another conclusion.